2004
DOI: 10.1007/s00038-004-3121-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the use of breast cancer screening services by women with intellectual disabilities

Abstract: The social trainers agreed that many of the barriers to screening would be difficult to overcome and supported alternative strategies to mammography, such as clinical breast examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…Although we could not identify mobility limitations as the cause of disability separately, it has also been found that individuals with mobility problems were as likely as others to receive pneumonia and influenza immunizations, but less likely to receive mammogram and Pap smear (Iezzoni et al, 2000). People with disabilities, especially intellectual disability, may experience more fear and anxiety about the cancer screening than the general population (Sullivan, Slack-Smith, & Hussain, 2004). Also like older people, people with disability have relatively shorter life expectancy and cancer screening may not be beneficial to them (Balducci, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not identify mobility limitations as the cause of disability separately, it has also been found that individuals with mobility problems were as likely as others to receive pneumonia and influenza immunizations, but less likely to receive mammogram and Pap smear (Iezzoni et al, 2000). People with disabilities, especially intellectual disability, may experience more fear and anxiety about the cancer screening than the general population (Sullivan, Slack-Smith, & Hussain, 2004). Also like older people, people with disability have relatively shorter life expectancy and cancer screening may not be beneficial to them (Balducci, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested alternative methods of screening (such as clinical breast examination)-methods which lack sufficient evidence for their use as screening tools in the general population. 35 Rates of breast cancer in women with ID reported in 2 large cohort studies are the same as or lower than the general population. 36,37 However, women with ID are living longer and because the risk of breast cancer rises with each decade of life, 38 the rates of breast cancer in women with ID will probably rise.…”
Section: Breast Cancer Screeningmentioning
confidence: 95%
“…Further, barriers to screening may exist for some patients with ID, such as anxiety, lack of understanding of the test, transportation problems, and the need for extra staff to accompany some patients from group homes to health care appointments. 5 To date, few documents exist with recommendations for screening; one was published by the Massachusetts Department of Mental Retardation. 6 These recommendations represent a consensus using standards from Massachusetts Health Quality Partners and a group of health professionals experienced in the care of adults with ID.…”
mentioning
confidence: 99%